EP867 Tumor suppression by FAT4 occurs by acting through retinoblastoma pathway in epithelial ovarian cancer. (1st November 2019) - Hanif, S; Al Moundhri, M; Burney, I; Tamimi, Y
Abstract : Introduction/Background: Epithelial ovarian cancer (EOC) accounts for about 70% of all types of ovarian cancer.It is a heterogeneous disease and has variable prognosis. In a previous study, chromatin immunoprecipitation (ChIP) was used to study expression of E2F5, a transcription factor, and revealed that FAT4, is regulated by E2F5. FAT4, a tumor suppressor gene, is an upstream regulator of the Hippo pathway and its expression in EOC remains unclear. Objective: We aimed to investigate the involvement of FAT4 gene in EOC by quantifying its expression in MCAS, OVSAHO, A2780cp and A2780s ovarian cancer cell lines and compare to HOSE, a normal ovarian cell line. Methodology: We evaluated the differential expression of FAT4 and E2F5 in five ovarian cancer cell lines using qRT-PCR and western blotting. We knocked down FAT4 and E2F5 in MCAS and OVSAHO using siRNA and monitored it at the mRNA and protein levels. The effect on viability and invasion following knockdown were assessed by alamar blue and invasion assay. The mechanism linking FAT4 and E2F5 was evaluated by assessing proteins involved in Hippo, Retinoblastoma and apoptotic pathways. Results: MCAS and OVSAHO showed higher FAT4 expression compared to A2780s and A2780cp. FAT4 and E2F5 were knocked down significantly using siRNA in MCAS (FAT4: p<0.01, E2F5: p<0.001) and OVSAHO (FAT4: p<0.001, E2F5: p<0.00001). Knockdown of FAT4 promoted cell viability, invasion, upregulation of mesenchymal markers (N-cadherin) and downregulation of epithelial markers (E-cadherin). Also, YAP, an oncogene involved in hippo pathway was upregulated while the pro apoptotic caspase 9 was down-regulated in FAT4 knocked cell lines. Further, Retinoblastoma and cdk4 was upregulated in E2F5 knocked compared to FAT4 knocked cells. Conclusion: Down regulation of FAT4 in ovarian cancer cell lines promotes growth and invasion via the modulation of apoptosis, Rb and Hippo pathways. Disclosure: Nothing to disclose.